2020
DOI: 10.3390/ani10040724
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Different Buffer Systems in Slurries Based on Time and Temperature of Storage and Their Visualization by a New Mathematical Tool

Abstract: Simple Summary: Efficient slurry management is a key strategy to reduce the release of environmentally harmful gases produced by farm animals. Slurry treatments such as acidification and alkalization have proven to be promising solutions to reduce these emissions. In this context, it is crucial to understand how buffer capacities behave and may influence each other during storage under the influence of different temperatures. To realize this, we have developed and successfully verified a new mathematical tool.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…The buffer effect of the deionized water was not considered because of its low ion content. The conversion processes and principles of action can also be detected in diluted slurry, as shown in previous studies [38]. The pH value and temperature of the slurry were both measured with the pH sensor 'InLab Expert Pro' (Mettler Toledo, OH, USA).…”
Section: Sampling and Storage Of Slurrymentioning
confidence: 92%
See 4 more Smart Citations
“…The buffer effect of the deionized water was not considered because of its low ion content. The conversion processes and principles of action can also be detected in diluted slurry, as shown in previous studies [38]. The pH value and temperature of the slurry were both measured with the pH sensor 'InLab Expert Pro' (Mettler Toledo, OH, USA).…”
Section: Sampling and Storage Of Slurrymentioning
confidence: 92%
“…The temperature during storage influences the progress of biodegradation processes, and thus also the pH value increase. The authors of [15] and [38] observed a faster pH increase during warm storage than during cold storage. This effect could not be considered in our investigation due to capacity constraints, therefore the storage was only carried out at laboratory temperature (approximately 22 • C).…”
Section: Ph Value During Storagementioning
confidence: 96%
See 3 more Smart Citations